Mice deficient in aldo-keto reductase 1a (Akr1a) are resistant to thioacetamide-induced liver injury. (15th September 2018) - Homma, Takujiro; Shirato, Takaya; Akihara, Ryusuke; Kobayashi, Sho; Lee, Jaeyong; Yamada, Ken-ichi; Miyata, Satoshi; Takahashi, Motoko; Fujii, Junichi
Highlights: Akr1a-deficient (Akr1a −/− ) mice are resistant to TAA-induced liver toxicity. The CYP2E1 activity in the Akr1a −/− mice is relatively lower compared to WT mice. The production of reactive TAA metabolites is suppressed in Akr1a −/− mice. The ER stress-induced apoptosis pathway is suppressed in Akr1a −/− mice. Abstract: Aldehyde reductase (Akr1a) has been reported to be involved in detoxification of reactive aldehydes as well as in the synthesis of bioactive compounds such as ascorbic acid (AsA). Because Akr1a is expressed at high levels in the liver and is involved in xenobiotic metabolism, our objective was to investigate the hepato-protective role of Akr1a in a thioacetamide (TAA)-induced hepatotoxicity model using Akr1a-deficient (Akr1a −/− ) mice. Wild-type (WT) and Akr1a −/− mice were injected intraperitoneally with TAA and the extent of liver injury in the acute phase was assessed. Intriguingly, the extent of TAA-induced liver damage was less in the Akr1a −/− mice than in the WT mice. Biomarkers for the ER stress-induced apoptosis pathway were markedly decreased in the livers of Akr1a −/− mice, whereas AsA levels in plasma did not change significantly in any of the mice. In the liver, TAA is converted to reactive metabolites such as TAA S-oxide and then to TAA S, S-dioxide via the action of CYP2E1. In Akr1a −/− mice, CYP2E1 activity was relatively lower than WT mice at the basal level, leading to reactive TAA metabolites being produced at lower levels after the TAA treatment. The levels of liver proteins that were modified with these metabolites were also lower in the Akr1a −/− mice than the WT mice after the TAA treatment. Furthermore, after a lethal dose of a TAA challenge, the WT mice all died within 36 h, whereas almost all of the Akr1a −/− mice survived. These collective results suggest that Akr1a −/− mice are resistant to TAA-induced liver injury, and it follows that the absence of Akr1a might modulate TAA bioactivation.